1956
DOI: 10.1507/endocrj1954.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Diphasic Action of Thyroxine Upon Succinic Dehydrogenase of Kidney Cortex, Heart Muscle, Adrenal Cortex, and Thyroid of Dog in Vitro

Abstract: Diphasicaction or dual effect of thyroxine, viz. activating effect in relatively low concentrations and inhibitory effect in higher concentrations, has been observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1959
1959
1966
1966

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…In accordance with previous reports by Sugisawa (6,7), that thyroxine action is diphasic upon succinic dehydrogenase of mouse and dog tissues, the present experiment, carried out under experimental conditions similar to those adopted by the author cited above, showed that T3, TA4, TA3, TP4 and TP3 also affect the same enzyme of mouse heart in a diphasic way.…”
Section: Commentssupporting
confidence: 92%
“…In accordance with previous reports by Sugisawa (6,7), that thyroxine action is diphasic upon succinic dehydrogenase of mouse and dog tissues, the present experiment, carried out under experimental conditions similar to those adopted by the author cited above, showed that T3, TA4, TA3, TP4 and TP3 also affect the same enzyme of mouse heart in a diphasic way.…”
Section: Commentssupporting
confidence: 92%